Effect of preemptive dexamethasone and etoricoxib on postoperative period following impacted third molar surgery - a randomized clinical trial - Rodrigues, Éwerton Daniel Rocha (Med Oral Patol Oral Cir Bucal, 2019)
BACKGROUND: The aim of this study was to compare the anti-inflammatory effects of dexamethasone and etoricoxib after third molar extraction. MATERIAL AND METHODS: A prospective, randomized, controlled, split-mouth study was conducted. 19 volunteers were allocated randomly to receive 90mg etoricoxib 1 hour prior to the procedure or 4mg intramuscular dexamethasone immediately after anesthesia. Baseline measurements were obtained preoperatively, and subsequent assessments were made on immediate postoperative, at 72 hours and 7 days after surgery to measure postoperative facial swelling by use of linear measurements, interincisal mouth opening width and visual analog scale score for pain. The amount of analgesics consumed was recorded. Descriptive statistics and the independent-samples t-test were used to compare the two groups at P < 0.05. RESULTS: Dexamethasone was effective in the control roasted edema for measurements of the mandibular angle - wing of the nose and mandibular angle - labial commissure 72 hours after surgery. And for the measurement mandibular angle - mentum, in the time of 72 hours and 7 days. There was no statistically significant difference in relation to pain and trismus. CONCLUSIONS: Considering significant results for some measures of the variable edema for the group that used intramuscular dexamethasone and the difference without statistical significance between groups for the other variables studied, we seem to reflect the intramuscular indication of the corticosteroid in a single dosage in relation to the use of etoricoxib as pre-emptive medication. Key words:Corticosteroids, COX-2 selective, third-molar surgery.